The evaluation of Human papilloma virus and human herpes viruses (EBV, CMV, VZV HSV‐1 and HSV‐2) in semen samples. (28th March 2021) - Tavakolian, Shaian; Goudarzi, Hossein; Nazarian, Hamid; Raee, Pourya; Niakan, Sarah; Faghihloo, Ebrahim
Abstract: There are a number of risk factors, especially viral diseases, which can lead to infertility. Among the various viral infections, much attention has been given to the role of the Papillomaviridae and Herpesviridae. After collecting 82 semen samples (37 teratospermia, 2 asthenozoospermia, 2 oligoasthenospermia, 1 oligospermia, 6 asthenoteratospermia and 34 normal semen samples), and washing them, the DNA from both freshly ejaculated spermatozoon and washed spermatozoa was extracted. Subsequently, the prevalence of EBV, CMV, HSV‐1, HSV‐2, VZV and HPV was evaluated using Multiplex PCR and Nested PCR. In this study, 1 normal and 5 abnormal semen samples were infected with HSV‐1 (1 normal, 4 teratospermia and 1 oligoasthenospermia). In addition, there were 2 VZV‐positive samples (both were teratozoospermia). Nested PCR indicated that 1 asthenozoospermia, 1 asthenoteratospermia, 3 teratospermia and 4 normal samples were HPV positive (including 8 HPV‐18 and 1 HPV‐33). Among 9 HPV‐positive subjects, 3 samples were negative after washing the infected samples. The prevalence of EBV, CMV, VZV, HSV‐1 and HSV‐2 remained unchanged prior to and after washing. Maybe sperm washing can be useful to eliminate HPV infection from semen samples, but further investigation is required because of the small number of samples.